iis suwartini SEKSUALITAS DALAM NOVEL DAN PUDARNYA NILAI MORAL BERDAMPAK PADA PENDIDIKAN (Universitas PGRI Adi Buana Surabaya, 2014)
The objectives of this research are to describe and explain (1) sexuality in novel, (2) the influence of sexuality in the novel to education. The research method was qualitative method. Qualitative method is research procedure that generates the description data in the form of word. The subject of the research was a novel that tells the sexual themes as Nyla, Saman, and the face of Vagina novel. The object of this study was sexuality in the novel. This research used radical feminism approach. The data collection of the research was non-interactive technique. Non-interactive technique was conducted intensive reading of novels and record-keeping actively with analysis content. Application of content analysis through reading stage, observes, interpret, and analyze novel. The validity of the data used data triangulation, and analysis techniques used non-interactive models, The influence of radical feminists creates novels by Indonesian women author more freedom to express their imagination so quit of social control. Women writers who have radical feminist are brave to adapt the taboo issue with vulgar language. It is of course contrary to the principle of literary works which have been proposed since Balai Pustaka period, at that time a literary work are expected to provide moral value. Furthermore, literary work becomes a part of education, especially language and Indonesian literature lessons. Therefore, the literature needs to inculcate the cultural values of the nation